Pengembangan Projek Penguatan Profil Pelajar Pancasila Melalui Addie Pada SMK Mega Link Majene - Abdul Latif; Herlina Ahmad; Asdar Asdar; Syamsuddin Syamsuddin (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2023)
This type of research is Research and Development (RnD). The development model refers to the ADDIE (Analyze, Design, Development, Implementation and Evaluation) model. The development of the Project for Strengthening the Pancasila Student Profile (P5) was implemented for class X students at SMK Mega Link Majene, this is in accordance with the implementation of the independent curriculum. The Pancasila student profile is an Indonesian student who is a lifelong learner who is competent, has character and behaves in accordance with Pancasila values. This research developed a project design from an assessment rubric, student reflection sheet, and teacher reflection sheet. Theme selection and project development selected 3 themes out of 8, including sustainable lifestyle, local wisdom, diversity, building body and soul, the voice of democracy, creating and using technology to build the Republic of Indonesia, work and work culture. The results of the research obtained that P5 Development can develop students' character, including having faith and devotion to God Almighty and having noble character, global diversity, working together, creative, critical reasoning and independence, especially on the theme: Build your body and soul by using Photoshop and Lifestyle applications. continuously using Canon 800D, Cam A11, Original Mirrolles Gimbal, Adobe Premiere, and the Bandicam application.